Factors affecting the level of parental knowledge about their children's congenital heart diseases and their care - Khaleel Ibrahim ALSuwayfee,; Eman Isam Muhammed,; Aws Hazem Al-Numan, (Journal of the Pakistan Medical Association, 2024)
Objective: To assess parental knowledge about their children's congenital heart disease using a newly-designed scale. Method: The cross-sectional study was conducted from June 2020 to May 2021, at Alkhansaa maternity and child hospital, Mosul Iraq; after approval from the ethics review committee of Ninevah Medical College, Ninevah University, Iraq, and comprised parents with children having congenital heart disease. Data, including age, gender, type of congenital heart disease as well as parents’ educational and socioeconomic levels, residence, internet use and knowledge of the disease with respect to type, burden, bacterial endocarditis, outcome, etc. was noted. Parental knowledge levels were measured using a self-designed scoring scale, having a total score of 18 and 4 categories; <6 = some knowledge, 7-12 = good knowledge, 13-17 = very good knowledge, and 18 = full knowledge. Data was analysed using SPSS 26. Results: There were 364 children with mean age 83.72±47.4 months and a male-female ratio of 0.98. The mean age at diagnosis was 12.1±8.32 months. The overall mean parental knowledge level was 8.41± 3.88, with 126(34.6%) parents having some knowledge, 178(48.9%) having good, 58(16%) having very good, and 2(0.5%) having full knowledge about their children’s health condition (p<0.001) There was a significant association of parental knowledge with educational level, socioeconomic status and the type of doctor caring for the child (p<0.05). The duration of the illness showed a significant correlation with knowledge level (p=0.021). Conclusion: The level of parental knowledge about congenital heart disease in children was not satisfactory. Key Words: Heart Defects, Congenital, Endocarditis, Bacterial, Social Class